2004
DOI: 10.1086/422731
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Hydrogen in Arp 158

Abstract: We present 21 cm observations of Arp 158. We have performed a study of the neutral hydrogen ( H i) to help us understand the overall formation and evolution of this system. This is a disturbed system with distinct optical knots connected by a linear structure embedded in luminous material. There is also a diffuse spray to the southeast. The H i seems to be made up of three distinct, kinematically separate systems. Arp 158 bears a certain optical resemblance to NGC 520 (Arp 157), which has been identified as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Such a virial mass is close to the molecular mass of Arp 105S for instance (Braine et al 2001). This mass is smaller than the total HI mass in C5 according to Iyer et al (2004). This is not surprising as the HI is more extended.…”
Section: Kinematics Of the Systemmentioning
confidence: 80%
See 3 more Smart Citations
“…Such a virial mass is close to the molecular mass of Arp 105S for instance (Braine et al 2001). This mass is smaller than the total HI mass in C5 according to Iyer et al (2004). This is not surprising as the HI is more extended.…”
Section: Kinematics Of the Systemmentioning
confidence: 80%
“…The HI data cube was obtained from the literature (Iyer et al 2004 Shallow near-infrared images of the system were obtained from the 2MASS (2 Micron All Sky Survey, Skrutskie et al 2006) archives. They are used exclusively for visual inspection.…”
Section: Himentioning
confidence: 99%
See 2 more Smart Citations
“…For several closely interacting/merging galaxy systems, a number of observational studies have revealed enhanced centrally condensed, as well as widely distributed neutral and molecular gas emissions (e.g., Gordon et al 2001;Casasola et al 2004;Iono et al 2005;Cullen et al 2007;Maybhate et al 2007). HI-observations of merging and interacting galaxies have also been carried out to probe the formation mechanisms of merging and interacting systems (e.g., Iyer et al 2004) and these observations provide vital kinematic information. On average, HI 21-cm emission has been detected from only 25−40% of merging and interacting galaxies observed (e.g.…”
Section: Introductionmentioning
confidence: 99%